(untitled) (Olhares, 2015)
The article presents to the Brazilian researchers Moroccan Aïcha Haroun El Yacoubi – playwright and theater director. Here the author recounts her participation in the International Festival of Body Expression, Theatre and Dance in Agadir, Morocco, coordinated in 2008 by Aïcha. Moreover, it deals with the exchanges it has with the artist, including the assembly of his play, Ghita, unpublished in Brazil.